THE STRATEGY OF ISLAMIC EDUCATION INSTITUTIONS IN IMPROVING THE QUALITY OF LEARNING IN THE DIGITAL ERA - sahri, sahri; akhyak, akhyak; Efendi, Nur; Muhajir, As’aril (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2023)
Education Quality Strategy is an effort to improve the quality of learning in the digital era. In the digital era, technology is an important tool in the learning process, so it requires transformation in the way of teaching and learning. This type of research uses literature research. This article discusses efforts to transform the quality of education to improve the quality of learning in the digital era. Some of the things discussed include the development of digital curricula that are relevant to the needs and goals, training and development of human resources, the use of technology to increase student interaction and interest in learning, as well as periodic evaluation and improvement. In the digital era, education quality transformation must pay attention to aspects of data security and privacy, as well as cooperation between related parties to ensure curriculum implementation in the digital era can run well and effectively.